The Canadian Geological Foundation – Supporting Geoscience in Canada - Swinden, H. (Geoscience Canada, 2010)
SUMMARY The Canadian Geological Foundation supports geoscience education, out-reach, promotion and public awareness in Canada through grants to organizations and individuals. Project proponents can apply to the Foundation for funding support. The Foundation’s members − prominent Canadian geo-scientists drawn from diverse backgrounds−review project proposals and allocate available resources annually to projects that meet the Foundation’s main objectives. CGF grants support a wide variety of projects, including geo-science books, teacher training, student activities and teaching aids, interpretative displays, conferences, and more. In addition to its general purpose endowments, the Foundation also receives and disburses money for specific purposes, including lecture tours, scholarships, and special projects.